Electronic Publishing Programs: Issues to Consider - Elizabeth W. Brown; Andrea L. Duda (Issues in Science and Technology Librarianship)
At first glance, the proliferation of Web journal publishing, particularly from the commercial sector recently, may seem like manna from heaven -- librarians can now offer users searchable full-text of important scientific journals, as well as enhancements found only in the electronic versions. When it comes to electronic publications, however, librarians must consider a host of details.